2020
DOI: 10.1016/j.injury.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Decision making in prehospital traumatic cardiac arrest; A qualitative study

Abstract: Background: Despite improving survival of patients in prehospital traumatic cardiac arrest (TCA), initiation and/or discontinuation of resuscitation of TCA patients remains a subject of debate among prehospital emergency medical service providers. The aim of this study was to identify factors that influence decision making by prehospital emergency medical service providers during resuscitation of patients with TCA.Methods: Twenty-five semi-structured interviews were conducted with experienced ambulance nurses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 15 publications
1
22
0
2
Order By: Relevance
“…We found that ethically relevant information primarily was related to the basic bioethical principles of autonomy and non-maleficence/beneficence. This finding is in line with previous research [ 4 , 6 , 11 , 38 , 39 ]. The assessment of the patients’ quality of life and the remaining length of life were predominant factors identified in this study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that ethically relevant information primarily was related to the basic bioethical principles of autonomy and non-maleficence/beneficence. This finding is in line with previous research [ 4 , 6 , 11 , 38 , 39 ]. The assessment of the patients’ quality of life and the remaining length of life were predominant factors identified in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Decision-making in prehospital resuscitation should ideally include both clinical and ethical considerations [ 9 ]. There is not much knowledge of the extent and quality of ethical considerations and their influence on resuscitation [ 10 , 11 ]. The European Resuscitation Council guidelines include the sub-category “Ethics of resuscitation and end of life decisions”.…”
Section: Introductionmentioning
confidence: 99%
“…The included papers contained data from 25 unique studies. Of these papers, 12 were qualitative studies [ 5 , 8 , 22 31 ], two mixed-method studies [ 32 , 33 ], and 13 quantitative studies [ 34 46 ]. The papers were published between 1993 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…As the field of resuscitation evolves, the context in which healthcare professionals make decisions changes. Recent studies describe new aspects, including non-medical factors, in decision-making in prehospital resuscitation [ 5 9 ]. We aimed to review original studies on non-medical factors that pre-hospital care providers describe as important for decision-making in adult resuscitation..…”
Section: Introductionmentioning
confidence: 99%
“…These injuries or injury sequelae can and should be addressed as soon as possible, preferably before the patient is transported to the hospital. Over the past years, the prehospital management of patients with TCA has gained a lot of attention in the Netherlands through more in depth education and training for both EMS and HEMS personnel, based on the latest European resuscitation committee guidelines (3). Whether this has led to survival rates comparable to those published in recent literature is currently unknown (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%